PRODUKSI TELUR BURUNG PUYUH (Coturnix-coturnix japanica) YANG DI BERI TEPUNG JEROAN IKANCAKALANG - Syukri Gubali; Srisukmawati Zainudin; Safriyanto Dako (Gorontalo Journal of Equatorial Animals, 2022)
Fish innards are waste from fish smoking areas and fish shelters that can be used as alternative feed ingredients in quail rations. This study aims to analyze the effect of feeding skipjack viscera in the ration to the appearance of quail in the grower phase. The research material used 160 quails aged 2 weeks. This study used a completely randomized design (CRD) with 5 trials and 4 replications. The treatments in this study were P0 (12% without skipjack viscera meal), P1 (3% skipjack viscera meal). P2 (6% of skipjack offal flour). P3 (9% skipjack offal flour). P4 (12% skipjack offal flour). Based on the results of the Analysis of Variance (ANOVA) it showed that the provision of steamed skipjack innards flour did not have a significant effect (P0.05) on egg production, ration consumption, ration conversion, shell thickness and index of width and length of quail eggs, but had a very significant effect. significantly (P0.05) on egg weight. The use of skipjack viscera flour can be used in quail rations up to 12% Keywords: Egg Production, Quail, Skipjack Offal